Enhanced efficiency of hybrid amorphous silicon solar cells based on single-walled carbon nanotubes and polymer composite thin film. (31st January 2018) - Rajanna, Pramod M; Gilshteyn, Evgenia P; Yagafarov, Timur; Alekseeva, Alena A; Anisimov, Anton S; Neumüller, Alex; Sergeev, Oleg; Bereznev, Sergei; Maricheva, Jelena; Nasibulin, Albert G
Abstract: We report a simple approach to fabricate hybrid solar cells (HSCs) based on a single-walled carbon nanotube (SWCNT) film and thin film hydrogenated amorphous silicon (a-Si:H). Randomly oriented high-quality SWCNTs with conductivity enhanced by means of poly(3, 4-ethylenedioxythiophene) polystyrene sulfonate are used as a window layer and a front electrode. A series of HSCs are fabricated in ambient conditions with varying SWCNT film thicknesses. The polymethylmethacrylate layer drop-casted on fabricated HSCs reduces the reflection fourfold and enhances the short-circuit J sc, open-circuit V oc, and efficiency by nearly 10%. A state-of-the-art J–V performance is shown for SWCNT/a-Si HSC with an open-circuit voltage of 900 mV and an efficiency of 3.4% under simulated one-sun AM 1.5 G direct illumination.